Aerial photography and videography using drones - Cheng, Eric (Peachpit Press, 2016)
Inexpensive consumer drones that offer ease of flight and high-quality photography and videography have exploded on the market recently, creating what can only be described as drone mania amongst a diverse range of potential users. Because camera-carrying drones still really only exist on the edge between hobby and the mainstream, there is still a lot of confusion about what these small drones are capable of doing. The decision to purchase one is just the first in a long stream of things a new owner must think about. Aerial Photography and Videography Using Drones is designed to help you make the most of the opportunities these nimble, affordable, and accessible flying machines have created for aerial photography and videography. Within this definitive guide, you'll learn about the following: • the current state of camera drone equipment • how to become a competent drone operator • tips for getting the best aerial still images and videos • stories from aerial photographers and videographers from around the world • the current regulatory state for drone usage in the U.S. • techniques demonstrated in several videos you can download from peachpit.com, along with pre-flight checklists and worksheets for flight training.